6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b
The given expression can be simplified to: 3b-a
a + 7b + 2c
It is: 19b+7b = 26b
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
It is: 7b+10 simplified
9a + 7b *remember to look and understand the letters!*
It is: 7b+4b-1b = 10b when simplified
4b plus 7b plus 5 will equal 11b plus 5. When you have two variables that are the same you can add the two numbers with the variables remaining the same.
a = b + 9; 4a = 7b so 4 x (b + 9) = 7b, ie 4b + 36 = 7b so b = 12 and a = 21
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
Well for me, it was 7b but for an average, run-of-the-mill school kid, it should be around 4a-5c.
2x + 7b is an expression. Since it is not an equation it cannot be solved. Furthermore, as an expression, there is no meaninful simplification, either.
(8b + 7)(7b + 9)
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
20a plus 14 will be 34a minus 8a minus 7 34a minus 8 is 26a minus 7 is 19a. The single b is 1b plus 6b which is 7b minus 2b equals 5b.
7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4
3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2
It is an equation and the value of b is 3